The Meaning Of The Respectful Attitude Of The Lamaholot People In The Short Story Koda By Silvester Petara Hurit - Wissang, Imelda Oliva (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
Abstract  This study aims to describe the meaning of respectful attitude of the Lamahholot community in the short story Koda by Silvester Petara Hurit. The attitude of life of the Lamaholot community, including the attitude of respect, is something that is inherent in the self, a habit that is carried out from generation to generation which describes the characteristics of the identity of the Lamaholot people who obediently maintain relationships with God, others, the universe, the environment, and themselves. The research method uses a qualitative descriptive method that intends to understand the phenomena experienced by the research subject such as behavior, perception, motivation, action, and others. The results of the study can be concluded that the meaning of the attitude of respect for the Lamahholot community in the short story Koda by Silvester Petara Hurit, as follows (1) the attitude of respect has the meaning of protecting, protecting, maintaining, guarding, (2) the attitude of obedience and obedience has the meaning of appreciating, accepting, recognizing, respecting, (3) courageous and critical attitude means openness, courage, responsibility to instill and maintain noble values such as honesty, (4) religious attitude means maintaining harmony, maintaining faith, openness, responsibility, and (5) attitude to maintain cultural heritage means respect, care, care and responsibility.  AbstrakPenelitian ini bertujuan mendeskripsikan makna sikap penghormatan masyarakat Lamahholot dalam cerpen Koda karya Silvester Petara Hurit. Sikap hidup masyarakat Lamaholot termasuk sikap penghormatan merupakan sesuatu yang melekat dalam diri, kebiasaan yang dijalankan turun temurun yang menggambarkan ciri identitas masyarakat Lamaholot yang taat menjaga hubungan dengan Tuhan, sesama, alam semesta, lingkungan, dan diri sendiri. Metode penelitian menggunakan  metode deskriptif kualitatif yang bermaksud memahami fenomena-fenomena apa yang dialami subjek penelitian misalnya perilaku, persepsi, motivasi, tindakan, dan lain-lain. Hasil penelitian dapat disimpulkan makna sikap penghormatan masyarakat Lamahholot dalam cerpen Koda karya Silvester Petara Hurit, sebagai berikut (1) sikap penghargaan memiliki makna melindungi, menjaga, memelihara, mengawal, (2) sikap patuh dan taat memiliki makna menghargai, menerima, mengakui, menghormati, (3) sikap berani dan kritis memiliki makna keterbukaan, keberanian, tanggung jawab menanamkan dan mempertahankan nilai-nilai luhur seperti kejujuran, (4) sikap religious memiliki makna menjaga keharmonisan, menjaga iman, keterbukaan, tanggung jawab, dan (5) sikap menjaga warisan budaya memiliki makna menghargai, menjaga, peduli dan tanggung jawab.